2020
DOI: 10.1093/jxb/eraa529
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor WRKY75 positively regulates jasmonate-mediated plant defense to necrotrophic fungal pathogens

Abstract: Necrotrophic fungi cause devastating diseases in both horticultural and agronomic crops, but our understanding of plant defense responses against these pathogens is still limited. In this study, we demonstrated that AtWRKY75 positively regulates the jasmonate (JA)-mediated plant defense against necrotrophic fungal pathogens Botrytis cinerea and Alternaria brassicicola and also affects plants’ sensitivity to JA-inhibited seed germination and root growth. Quantitative RT-PCR analysis indicated that the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 78 publications
1
65
0
Order By: Relevance
“…GhJAZ2 interacted with GhbHLH171 to restrain the JA-mediated defense response to the fungus Verticillium dahliae in cotton [194]. JAZ8 repressed the transcriptional function of WRKY75, whereas JAZ8 overexpression repressed plant defense responses to necrotrophic pathogens in Arabidopsis [195]. These results demonstrate that resistance against necrotrophic pathogens can be strengthened by JA signaling-related genes (Figure 7).…”
Section: Plant Disease Resistancementioning
confidence: 83%
“…GhJAZ2 interacted with GhbHLH171 to restrain the JA-mediated defense response to the fungus Verticillium dahliae in cotton [194]. JAZ8 repressed the transcriptional function of WRKY75, whereas JAZ8 overexpression repressed plant defense responses to necrotrophic pathogens in Arabidopsis [195]. These results demonstrate that resistance against necrotrophic pathogens can be strengthened by JA signaling-related genes (Figure 7).…”
Section: Plant Disease Resistancementioning
confidence: 83%
“…In particular, JAs display inhibitory effects on primary root growth [12][13][14]. On the other hand, JAs positively regulate stamen development [15], male and female fertility [16,17], anthocyanin biosynthesis [17,18], and defense against insects and necrotrophic pathogens [1,19]. Multiple roles of JA in maize are best illustrated in the study of the opr7opr8 double mutant, which is deficient in JA biosynthesis, is male-sterile, lacks anthocyanin production, and is susceptible to soil-borne pathogen Pythium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this speculation, we found that the concentrations of JA-Ile were significantly lower in the Mj2G02transgenic Arabidopsis lines than in WT plants. Moreover, the expression levels of four JA-responsive genes, MYC3, UPI, THI2.1, and WRKY75, which have been reported to be involved in plant defence against plant pathogens (Chen et al, 2020;Fernandez-Calvo et al, 2011;Kammerhofer et al, 2015;Laluk & Mengiste, 2011), were also significantly reduced in the Mj2G02-transgenic Arabidopsis lines.…”
Section: Discussionmentioning
confidence: 96%